THE EFFECTIVENESS OF ISLAMIC MUSIC THERAPY ON LANGUAGE ABILITY IN AUTISTIC CHILDREN AGED 6-11 YEARS - Fitri Romadonika, Fitri Romadonika; Rias Pratiwi Safitri, Rias Pratiwi Safitri; Dian Istiana, Dian Istiana; Reza Rahmana, Reza Rahmana (Universitas Islam Negeri Alauddin Makassar, 2022)
United Nations Educational, Scientific, and Cultural Organization (UNESCO) data in 2011 asserted that around 35 million people worldwide were autistic. In Indonesia, the Director of Mental Health Development under the Ministry of Health suspected that about 112.000 children ages 5-19 years were affected by this disease. This research aimed to determine the effectiveness of Islamic song therapy toward language ability in autistic children ages 6-11 years. This research method used a pre-experiment with one group pre-test and post-test design approach with autistic children with as many as 16 people. The research samples were eight respondents (purposive sampling technique). The method of data collection used in this research was Massey Language Test. Based on the results, Islamic song therapy effectively improves language ability in autistic children. Recommendations that the researcher delivered to readers, Islamic song therapy can be included in learning in schools and applied in the department of nursing, especially to children subject with special needs, further deepening the practice of providing Islamic song therapy to autism. Keywords: Islamic Music therapy, Language Ability, Autism